(untitled) (Journal of Management and Business Education, 2021)
Entrepreneurship education aims to contribute to the emergence of innovative skills, abilities, and competencies in people, in the most diverse sectors and branches of activity of contemporary society, regardless of the intention to establish a new start-up. This study explores the development of entrepreneurial competencies, intentions and attitudes offered by a higher education institution through the adoption of the eValueComp assessment tool. It offers significant contributions to the business education field particularly aimed at higher education professors who intend to place the student in a more active position and provide an entrepreneurial education, which will be useful for their future professional career. The findings revealed a significant increase of entrepreneurial competencies, general entrepreneurial attitudes, and perception of entrepreneurial feasibility. However, entrepreneurial intentions have evolved only marginally. Furthermore, the age and number of years of professional experience are two correlated factors that contribute to students having a greater perception of the risks associated with the entrepreneurship process.